Essay on the constitutional promises of democracy and republic - Salgado, Eneida Desiree (Revista de Investigações Constitucionais, 2017)
This essay aims at explaining what the democratic and republican principles declared in the Brazilian Constitution represent – or could represent. First, the work considers the notion of a Constitution and its models, combined with the concept of rule of law. The author goes further and examines the idea of freedom, as it changes depending on the constitutional model followed, be it derived from the French or the American Revolution. Presenting the preoccupations of different experts regarding a constitutional system, the essay compares their arguments before considering the elements of the Brazilian Constitution and its preamble. In this context, it is made clear the influence of Brazilian History in the understanding of the meaning of democracy and republic in the country. Furthermore, concepts such as “individual”, “citizen”, “citizenship”, “government”, “equality”, “communitarianism”, “solidarity”, “common good”, “vote”, among others, are all presented and understood through the lenses of the Brazilian Constitution and constitutional doctrine to build a wide-ranging yet comprehensible notion of democracy and republic in Brazil.